Increased mean aliphatic lipid chain length in left ventricular hypertrophy secondary to arterial hypertension: A cross-sectional study. Issue 46 (November 2016) - Evaristi, Maria Francesca; Caubère, Céline; Harmancey, Romain; Desmoulin, Franck; Peacock, William Frank; Berry, Matthieu; Turkieh, Annie; Barutaut, Manon; Galinier, Michel; Dambrin, Camille; Polidori, Carlo; Miceli, Cristina; et al.
Abstract : Abstract: About 77.9 million (1 in 4) American adults have high blood pressure. High blood pressure is the primary cause of left ventricular hypertrophy (LVH), which represents a strong predictor of future heart failure and cardiovascular mortality. Previous studies have shown an altered metabolic profile in hypertensive patients with LVH. The goal of this study was to identify blood metabolomic LVH biomarkers by 1 H NMR to provide novel diagnostic tools for rapid LVH detection in populations of hypertensive individuals. This cross-sectional study included 48 hypertensive patients with LVH matched with 48 hypertensive patients with normal LV size, and 24 healthy controls. Two-dimensional targeted M-mode echocardiography was performed to measure left ventricular mass index. Partial least squares discriminant analysis was used for the multivariate analysis of the 1 H NMR spectral data. From the 1 H NMR-based metabolomic profiling, signals coming from methylene (–CH2 –) and methyl (–CH3 ) moieties of aliphatic chains from plasma lipids were identified as discriminant variables. The –CH2 –/–CH3 ratio, an indicator of the mean length of the aliphatic lipid chains, was significantly higher ( P < 0.001) in the LVH group than in the hypertensive group without LVH and controls. Receiver operating characteristic curve showed that a cutoff of 2.34 provided a 52.08% sensitivity and 85.42% specificity for discriminating LVH (AUC = 0.703, P -value < 0.001). We propose the –CH2 –/–CH3 ratio from plasma aliphatic lipid chains as a biomarker for the diagnosis of left ventricular remodeling in hypertension.